2019
DOI: 10.2196/12667
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Communication Interchange of Individuals With Disabilities Utilizing Facebook, Discussion Forums, and Chat Rooms: Qualitative Content Analysis of Online Disabilities Support Groups

Abstract: BackgroundApproximately 1 in 5 adults in the United States are currently living with a form of disability. Although the Americans with Disabilities Act has published guidelines to help make developing technology and social networking sites (SNS) more accessible and user-friendly to people with a range of disabilities, persons with disabilities, on average, have less access to the internet than the general population. The quality, content, and medium vary from site to site and have been greatly understudied. Du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Social media is increasingly being used by health services to encourage the growth of social support networks among people with health-related issues [1,2]. Through participation on different platforms, patients are able to provide and receive social support in various ways, without the typical barriers and constraints experienced by this population [3]. In this way, problems of information asymmetry, as well as the shortages and uneven distribution of medical resources can be alleviated [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Social media is increasingly being used by health services to encourage the growth of social support networks among people with health-related issues [1,2]. Through participation on different platforms, patients are able to provide and receive social support in various ways, without the typical barriers and constraints experienced by this population [3]. In this way, problems of information asymmetry, as well as the shortages and uneven distribution of medical resources can be alleviated [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In another study applying word2vec in small corpora using the semantic categorization test, Stetten, the study included 37 k and 140 k documents to analyze and disambiguate the content of dreams [102]. This research area addresses questions such as "How do gender, cultural background, and waking life experiences shape the content of dreams?".…”
Section: Discussionmentioning
confidence: 99%
“…Facebook groups, discussion forums, and chat rooms were recently analyzed [ 63 ] to explore and compare the interactions and connections among online support groups to better understand how people with disabilities were utilizing different social networks to facilitate communication interchange. They concluded that through participation on different platforms, persons with disabilities are able to provide and receive social support in various ways, without the barriers and constraints often experienced by this population.…”
Section: Discussionmentioning
confidence: 99%